Harnessing Hazara Virus as a Surrogate for Crimean–Congo Hemorrhagic Fever Virus Enables Inactivation Studies at a Low Biosafety Level - Judith Olejnik; Kristina Meier; Jarod N. Herrera; Daniel J. DeStasio; Dylan J. Deeney; Elizabeth Y. Flores; Mitchell R. White; Adam J. Hume; Elke Mühlberger (Pathogens)
Research on highly pathogenic biosafety level 4 (BSL-4) viruses that are classified as Select Agents involves transferring inactivated materials to lower containment levels for further analysis. Compliance with Select Agent and BSL-4 safety regulations necessitates the validation and verification of inactivation procedures. To streamline this process, it would be beneficial to use surrogate BSL-2 viruses for inactivation studies. This not only simplifies BSL-4 work but also enables the testing and validation of inactivation procedures in research facilities that lack access to high-containment laboratories yet may receive samples containing highly pathogenic viruses that require efficient and complete inactivation. In this study, we used Hazara virus (HAZV) as a surrogate virus for Crimean–Congo hemorrhagic fever virus to show the efficacy of various inactivation methods. We demonstrate the successful inactivation of HAZV using TRIzol/TRIzol LS and aldehyde fixation. Importantly, the parameters of the aldehyde inactivation of cell pellets differed from those of the monolayers, highlighting the importance of inactivation validation. As part of this study, we also defined specific criteria that must be met by a BSL-2 virus to be used as a surrogate for a closely related BSL-4 virus. Defining these criteria helps identify suitable nonpathogenic surrogates for developing inactivation procedures for highly pathogenic viruses.